Exposure to the COVID-19 Stock Market Crash and Its Effect on Household Expectations - Hanspal, Tobin; Weber, Annika; Wohlfart, Johannes (The Review of Economics and Statistics, 2021)
We survey a representative sample of U.S. households to study how exposure to the COVID-19 stock market crash affects expectations and planned behavior. Wealth shocks are associated with upward adjustments of expectations about retirement age, desired working hours, and household debt but have only small effects on expected spending. We provide correlational and experimental evidence that beliefs about the duration of the stock market recovery shape households' expectations about their own wealth and their planned investment decisions and labor market activity. Our findings shed light on the implications of household exposure to stock market crashes for expectation formation.